2017
DOI: 10.15171/jcvtr.2017.29
|View full text |Cite
|
Sign up to set email alerts
|

Association of the rs555172 polymorphism in SENCR long non-coding RNA and atherosclerotic coronary artery disease

Abstract: Introduction: Variants in long non-coding RNAs (lncRNAs) have been implicated as potential biomarkers in prediction of complex disorders such as coronary artery disease (CAD). Studies considering the impact of the SENCR antisense lncRNAs on CAD have not established yet in Iranian population. This study aimed to investigate the association between SENCR rs555172 polymorphism and CAD in south Iranian population. Methods: Amplification refractory mutation system-polymerase chain reaction (ARMS-PCR) was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Gao et al reported that the risk rs2067051A allele in lncRNA- H19 was more frequent in CAD patients than in controls [ 20 ]. Shahmoradi et al reported that the frequency of rs555172 GG genotype in lncRNA9 was significantly higher among female CAD patients compared to male patients [ 24 ]. In this study, we found a reduced risk of rs619586 AG/GG genotypes in MALAT1 with CAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al reported that the risk rs2067051A allele in lncRNA- H19 was more frequent in CAD patients than in controls [ 20 ]. Shahmoradi et al reported that the frequency of rs555172 GG genotype in lncRNA9 was significantly higher among female CAD patients compared to male patients [ 24 ]. In this study, we found a reduced risk of rs619586 AG/GG genotypes in MALAT1 with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that single nucleotide polymorphisms (SNPs) in lncRNA contribute to the risk of CAD [ 18 – 24 ]. We therefore hypothesized that SNPs in MALAT1 may be related to the individuals’ susceptibility to CAD.…”
Section: Introductionmentioning
confidence: 99%
“…By using amplification refractory mutation system-polymerase chain reaction, SENCR can be detected stably and sensitively in blood samples of patients with CAD (Shahmoradi et al, 2017). Besides, a large-scale investigation focused on the effect of pioglitazone on type 2 diabetes found that the expression of SENCR in the blood is related to the evaluation of diastolic function after drug treatment, and that its indication in drug treatment effect is better than other existing indicators (De Gonzalo-Calvo et al, 2016b).…”
Section: Sencr (Smooth Muscle and Endothelial Cell-enriched Migrationmentioning
confidence: 99%
“…By using amplification refractory mutation system-polymerase chain reaction, SENCR can be detected stably and sensitively in blood samples of patients with CAD (Shahmoradi et al 2017). Besides, a large-scale investigation focused on the effect of pioglitazone on type 2 diabetes found that the expression of SENCR in the blood is related to the evaluation of diastolic function after drug treatment, and that its indication in drug treatment effect is better than other existing indicators (de Gonzalo-Calvo et al 2016b).…”
Section: Sencr (Smooth Muscle and Endothelial Cell-enriched Migrationmentioning
confidence: 99%